The Role of physical activity and nutrition in managing pain, fatigue, and inflammation in endometriosis - Dmowska, Dominika; Zdebski, Paweł; Rymska, Karolina; Gloc, Ewa; Ejsner, Rafał; Kaczmarek, Marcelina; Mierniczek, Mateusz; Mierniczek, Maria; Załęski, Daniel; Lewandowski, Mikołaj; Bilińska, Aleksandra (Quality in Sport, 2026)
Endometriosis is a highly prevalent inflammatory disease that affects millions of women. Endometriosis affects between 10-15% of women of reproductive age globally what is representing nearly 180 million cases worldwide. In Poland alone, the number of sufferers reaches 3 million. Its diagnosed much more frequently among women seeking treatment for fertility problems. That’s estimated more than half of them may have a sign of endometriosis. Currently used medications only reduces the symptoms of the disease, which is why the interdisciplinary aspect in the context of endometriosis is so important, as is the attempt to alleviate the course of the disease through alternative methods like balanced diet and physical activity. In this study, we focused on examining the impact of physical activity on the course of endometriosis. Materials and methods: The review was conducted using publications published in the PubMed, Google Scoolar and UpToDate. Our search included the following keywords: pain, endometriosis, quality of life, fatigue, fertility, physical activity. We based on literature published between 2008-2025. Results: According to the survey and literary reports physical activity significantly improves the quality of life of patients affected by endometriosis. Physical activity significantly improves the quality of life of patients with endometriosis. This positive impact is felt both physically and mentally, which is often disturbed by this condition.